Analysis of Trends and Composition of Forest and Vegetative Land Rehabilitation Activities in the Limboto Lake Catchment Area for the Period 2021-2025 - Sitti Mutiah Rahman; Iswan Dunggio; Sukirman Rahim (West Science Interdisciplinary Studies, 2026)
This study analyzes the temporal trend and activity composition of vegetative forest and land rehabilitation (RHL) in the catchment area of Lake Limboto for 2021–2025. A quantitative descriptive approach was applied to secondary data from the BPDAS Bone Limboto 2025 database, strengthened with year-on-year change rates, the coefficient of variation, concentration ratios, and the Herfindahl-Hirschman index to assess the program portfolio structure. The total area of vegetative RHL over five years reached 693 ha, with an annual mean of 138.6 ha and a coefficient of variation of about 79.9%, indicating a dynamic, phase-based implementation rhythm. The highest achievement occurred in 2022 (340 ha; 49.06%), while the two leading years (2022–2023) accounted for 74.31% of the total. By composition, core RHL planting dominated (262 ha; 37.81%), followed by watershed rehabilitation (200 ha; 28.86%) and the Community Nursery/KBR (183 ha; 26.41%); these three pillars formed 93.07% of the portfolio, with an effective number of activities of 3.33. The annual composition revealed a tiered pattern from seedling provision toward larger-scale planting. Spatial interpretation of the activity map showed interventions concentrated on the buffer hill belts to the north, west, and south of the catchment, consistent with an upstream-priority logic. The findings emphasize that RHL evaluation should consider temporal continuity and compositional balance, not only area achievement.